Successful Endoscopic Removal of Anisakis Larva that Deeply Invaded the Gastric Mucosa Using Jumbo Forceps - Toshio Arai; Takehito Kunogi; Takahiro Kinebuchi; Yasuhiro Nakano; Koji Nishikawa; Hiromu Sugiyama (Case Reports in Gastroenterology, 2023)
Anisakiasis is a parasitic disease caused by the ingestion of raw or uncooked seafood infected with third-stage larvae of anisakid nematodes. Generally, the larvae parasites live at the surface of the mucosa, but in this case, the larva deeply invaded its head into the gastric mucosa and was not removable with conventional biopsy forceps. In our case, we demonstrated the usefulness of jumbo forceps to remove the Anisakis larva in such a situation.